A study on the use of contraception and its effects on breastfeeding among women at maternal and child health clinic - Al-Araji, Laith Issa Yassin; Wan Su, Kamaruzaman (2011)
Breastfeeding, when practiced in a specific way, can be used to prolong the period of post-partum infertility. However, there are still chances to get pregnant if certain criteria of Lactational Amenorrhea Method (LAM) were not met. Nursing mothers need to ensure the birth control they choose is safe for the mother and the baby. A cross-sectional study was conducted to determine the association between the contraceptive methods and breastfeeding practice and also to know the relationship between demographic data and the reasons for contraception. 50 nursing mothers were involved in this study, and they were conveniently taken from the Maternal and Child Health Clinic of Beserah, Kuantan. All the data were collected using a questionnaire which consists of three parts. It was found that most of the participants (18) choose to use OCPs (Oral Contraceptive Pills) as their birth control method. In addition, there was an association between contraceptive methods used by the respondents with the effects on breastfeeding practice where the P value is 0.048. Apart from it, there was no significant association between demographic data (Age, Educational Level, Household Income, Working Status and Total number of Children) and the reasons for contraception among the respondents. 32 respondents (64%) have started using contraception after six weeks of delivery and the main sources of information regarding contraception are the healthcare providers (80%). These findings indicated that the methods of contraceptive chosen by the respondents are correlated with the breastfeeding practice.